Gut-Liver Axis Derangement in Non-Alcoholic Fatty Liver Disease - Marco Poeta; Luca Pierri; Pietro Vajro (MDPI AG, 2017)
Non-alcoholic fatty liver disease (NAFLD) is the most frequent type of chronic liver disease in the pediatric age group, paralleling an obesity pandemic. A "multiple-hit" hypothesis has been invoked to explain its pathogenesis. The "first hit" is liver lipid accumulation in obese children with insulin resistance. In the absence of significant lifestyle modifications leading to weight loss and increased physical activity, other factors may act as "second hits" implicated in liver damage progression leading to more severe forms of inflammation and hepatic fibrosis. In this regard, the gut-liver axis (GLA) seems to play a central role. Principal players are the gut microbiota, its bacterial products, and the intestinal barrier. A derangement of GLA (namely, dysbiosis and altered intestinal permeability) may promote bacteria/bacterial product translocation into portal circulation, activation of inflammation via toll-like receptors signaling in hepatocytes, and progression from simple steatosis to non-alcoholic steato-hepatitis (NASH). Among other factors a relevant role has been attributed to the farnesoid X receptor, a nuclear transcriptional factor activated from bile acids chemically modified by gut microbiota (GM) enzymes. The individuation and elucidation of GLA derangement in NAFLD pathomechanisms is of interest at all ages and especially in pediatrics to identify new therapeutic approaches in patients recalcitrant to lifestyle changes. Specific targeting of gut microbiota via pre-/probiotic supplementation, feces transplantation, and farnesoid X receptor modulation appear promising.